Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Cumulative Review - Page 565: 46



Work Step by Step

$4x^{2}+12x+9$ =$4x^{2}+6x+6x+9$ =$2x(2x+3)+3(2x+3)$ =$(2x+3)(2x+3)$ =$(2x+3)^{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.